Understanding the industrial designer's self-perception of ideation. Issue 4 (1st October 2020) - Sun, Ying; Münster, Sander; Köhler, Thomas; Sommer, Carlo Michael
ABSTRACT: As an essential step, design ideas generation is a process rooted in personal knowledge with a precedent-based type of reasoning, where knowledge is constantly transformed to develop new insights. An outstanding challenge in industrial design is transforming the inspirational source into insights that inform design. Based on the grounded theory, an open-ended semi-structured qualitative interview was conducted with professional industrial designers, to uncover what sources and methods do they choose and how do they transform the generated insights to ideas and the design mind-set involved. A compact framework and a detailed instrument paradigm were developed, which helps novice and students designers to explore creative solutions during the ideation process.